Sol-gel derived ZnO film as a gas sensor: Influence of UV processing versus a thermal annealing - Pronin, Igor A.; Plugin, Ilia A.; Kolosov, Dmitry A.; Karmanov, Andrey A.; Yakushova, Nadezhda D.; Varezhnikov, Alexey S.; Komolov, Alexey S.; Lazneva, Eleonora F.; Koroleva, Aleksandra V.; Moshnikov, Vyacheslav A.; Kondratev, Valeriy M.; Glukhova, Olga E.; et al. (Sensors and actuators. A. Physical., 2024)
While preparing oxide layers as gas sensors by a sol-gel approach, a high-temperature annealing makes a challenge to apply in numerous applications like flexible electronics with a heavy influence on the oxide microstructure. Therefore, its replacing by UV irradiation combined with a mild heating as “photo-annealing” paves the way to develop soft protocols when designing oxide-based gas sensors bearing a fine nanocrystallinity. Herein, we consider hierarchical sol-gel derived ZnO films which were a subject of conventional annealing and photoannealing to compare their gas-sensor performance when exposed to alcohol vapors. It is found that films obtained by photoannealing have an X-ray amorphous character, in contrast to ones being thermally annealed; although, the hierarchical organization of both samples revealed by SEM is almost identical. The DFTB modeling performed for ZnO crystal exposed to alcohol molecules and water has indicated the chemiresistive effect to be enhanced with a molecular weight of analytes. These observations were validated in experiment with sol-gel ZnO layers which exhibited an alcohol response in sub-ppm concentration range down to 10 ppb. To selectively compare the impact of various alcohols, we successfully applied a linear-discriminant analysis to the vector signal of the on-chip multisensor array. [Display omitted] •ZnO nanocrystalline layers were fabricated by annealing and UV irradiation/mild heating.•Photoannealed ZnO exhibited finer crystallinity than thermal-treated samples under same morphology.•The both-type ZnO layers exhibited a sensitivity to alcohol vapors down to 10 ppb concentration.•The alcohol response of ZnO layers matches results of DFT calculations.